Development Model of Sago Agroindustry Small and Medium Enterprises (SMEs) In Southeast Sulawesi Province: Income and Strategy Analysis - Purbaningsih, Yuli; Nursalam; Prihantini, Campina Illa; Hasbiadi; Karim, Ahmad Tarmizi Abd; Sejati, Andri Estining (HABITAT, 2023)
Sago plants are the main staple food in Southeast Sulawesi. Sago plants have various economic value for bioethanol, roofs, and carbohydrates. Community managed sago plantations by using an agro-industrial model. Although, sago processing has long been developed, but the community is still living in a low socio-economic condition. The allocation of sago agro-industry production factors is still not optimal, resulting in a fluctuative production, quality and productivity. This study analyzed the income of the sago agroindustry and formulated a strategy for the sago agroindustry development. The study was conducted in Konawe Regency, Southeast Sulawesi Province. Sampling in this study was carried out by purposive sampling and total sampling. The analytical methods used include income analysis to analyze the income of the sago agroindustry, SWOT analysis to formulate strategies for the development of the sago agroindustry. The results showed that the income level of Konawe Regency’s sago agroindustry in a monthly sago processing was Rp. 14,205,770. The analysis results of sago agroindustry development strategy in Konawe Regency obtain five core strategies, focusing on packaging and labeling, production and marketing, training in seedling and management of the sago agroindustry, land conversion policy and sago price policy, and the sago agroindustry partnership program.